First-principles study of ferromagnetic, optical, and transport properties of double Perovskites Z2FeTiO6 (Z = Mg, Zn). (1st April 2022) - Ghrib, Taher; Flemban, Tahani H; Alshahrani, Thamraa; Bouzgarrou, S; Ercan, Filiz; Mera, Abeer; Somaily, H H; Mahmood, Q
Abstract: Spintronics is an emerging technology in which electron spin carries information along with its charge. The current article reveals the ferromagnetic, optical, and thermoelectric properties of Z2 FeTiO6 (Z = Mg, Zn) predicted using the first-principles calculations. Heisenberg's classical model and polarization density calculations ensure ferromagnetism above room temperature and 100% spin polarization. Besides, the nature of ferromagnetism has been addressed by s-d and p-d exchange splitting, double exchange model, exchange energies, crystal field energy, and exchange constants. Furthermore, the optical properties are elaborated by dielectric constant, refractive index, and absorption in which intra-band transitions are incorporated. Finally, the thermal transports of the materials are investigated in terms of electrical and thermal conductivities, Seebeck coefficient, and power factor.